Islamic worldview-based corporate governance framework in providing guidance on Executive Directors’ remuneration in an Islamic financial institution - Uddin, Md Nazim; Haque, A. K. M. Ahasanul (IGI Global Business Science Reference, 2023)
This chapter addresses how corporate governance supports shareholder-director conflicts and company success. Islamic financial institution (IFI) governance and performance have not been studied, yet corporate governance has affected previous financial crises. This examines IFI board size, ownership, CEO duality, and pay committee independent directors. Also studied is how Islamic corporate governance influences executive director pay. Thus, IFIs require an IWBCGF to handle current and future corporate governance issues. Qualitative corporate governance metrics research and qualitative Islamic principle evaluation helped exploratory studies attain these goals. The research shows that corporate governance strongly impacts IFI executive pay. These results show that executive directors require an Islamic-based comprehensive governance framework to navigate corporate governance issues. The study makes literary contributions. It tackles the lack of religious research on Islam and IFI corporate governance. It highlights IFIs’ corporate governance and CEO remuneration.